Estrogen upregulates renal angiotensin II AT1 and AT2 receptors in the rat - Baiardi, Gustavo Carlos (2004)
We studied renal AT1 and AT2 receptors in male, female, ovariectomized and ovariectomized-estrogen-treated Wistar-Hanover and Wistar-Kyoto rats. AT1 receptors and AT1A receptor mRNA predominated, with no significant differences between males and females. AT 2 receptor expression was restricted in female rats to the capsule, the transition zone between outer and inner medulla, the endothelium lining the papilla, and arcuate arteries and veins. There were no AT2 receptors in male rats, while male mice express substantial numbers of estrogen-dependent AT2 receptors. Arcuate arteries and veins expressed AT1B mRNA in males and females, and AT2 mRNA in females only. AT 1 receptor and AT2 receptor expression were estrogen-dependent, with increases in AT1 and AT2 receptor expression after estrogen treatment in ovariectomized rats. Estrogen treatment increased prostaglandin E2 (PGE2) and cGMP concentrations in the renal medulla, and eNOS expression in cortical arteries. In rodents, expression of renal Angiotensin II receptor types is estrogen-dependent, with significant species, strain and area differences. Our results support an important role for AT2 receptors in the regulation of renal function and in the protective effects of estrogen in the kidney. © 2004 Published by Elsevier B.V.